2022
DOI: 10.1007/s00216-022-03939-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial ligands as flexible and sensitive detectors in rapid tests for antibodies to SARS-CoV-2

Abstract: Lateral flow immunoassay (LFIA) is widely employed as point-of-care tests (POCT) for the diagnosis of infectious diseases. The accuracy of LFIA largely depends on the quality of the immunoreagents used. Typical LFIAs to reveal the immune response to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) employ anti-human immunoglobulin (hIG) antibodies and recombinant viral antigens, which usually are unstable and poorly soluble. Broad selective bacterial proteins, such as Staphylococcal protein A (SpA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The following supporting information can be downloaded at: . Chemicals, AuNP synthesis, flocculation test [ 32 ]. Figure S1: Flocculation stress test for the mAb #2C6 (a) and for the mAb #2F10 (b).…”
mentioning
confidence: 99%
“…The following supporting information can be downloaded at: . Chemicals, AuNP synthesis, flocculation test [ 32 ]. Figure S1: Flocculation stress test for the mAb #2C6 (a) and for the mAb #2F10 (b).…”
mentioning
confidence: 99%
“…The fast (30 min) and sensitive detection of SARS-CoV-2 antibodies was recorded with a LOD of 1 ng/mL that enabled the application of the sensor only in serum samples as for human nasopharyngeal swabs the values of IgG and IgM go down to pg/mL [ 144 ]. Unlike lateral flow immunoassay (LFA) platforms where multiple antibodies are exploited in charge of the reporter, no antibodies are required if label-free electrochemical systems are applied [ 150 ]. Although sensitive and cost-effective, ePADs fail to accurately and uniformly control the flow rate that dramatically influences the performance of the sensor.…”
Section: Biomarkers Involved In Inflammatory Diseasesmentioning
confidence: 99%
“…Among these, we mention the high sensitivity ensured by the easy functionalization with nanomaterials, the high selectivity when using biological or biomimetic elements, the fast response, but especially their suitability for miniaturization and automation, basic properties in the field of POCT sensing devices. It can be observed that only one example of detection devices does not meet the criteria “Specific” [ 36 ], respectively, “Sensitive” [ 150 ], which can be a justification for the large number of recent studies that include electrochemical sensors and biosensors aimed at the development of POCT devices for biomedical and clinical practice, where real, biological samples are very complex in composition and usually contain very low concentrations of analytes.…”
Section: Conclusion Future Perspectives and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serodiagnosis is typically implemented using immunoglobulin-binding proteins, such as anti-species antibodies or bacterial protecting compounds (staphylococcal protein A, streptococcal protein G, etc.) [ 16 ]. In the common LFIA format, they are immobilized on colored nanoparticles, applied on a test strip, and form complexes with all immunoglobulins, including those specific to the target pathogen during lateral flow.…”
Section: Introductionmentioning
confidence: 99%